Maintenance of South Estonian Varieties: A Focus on Institutions - Kadri Koreinik; Evar Saar (Journal on Ethnopolitics and Minority Issues in Europe, 2012)
Institutions are seen as the societal rules of the game in the broadest sense. Institutions include informal norms and formal laws, which are not necessarily functional, but shape human interaction by both prohibiting and enabling it. In language maintenance, too, institutions can serve as obstacles or can provide support, for example through additional resources. In our article, both the normative and legal aspects of language maintenance are presented and discussed on the basis of the example of South Estonian. Although its varieties-Setu and Voru-are traditionally grouped into one category of sub-language, the speakers' senses of identity and different cultural practices lead to objections to this exclusively linguistic branching. We discuss how, given the similar linguistic resources the Seto and Voru speech communities possess, norms and laws concerning varieties of South Estonian have been maintained and whether they have changed.